Heat Response Model for Phase Layered Topology in A Photovoltaic Thermal System - Mohammad Taghi Hajibeigy; Chockalingam Aravind Vaithilingam; Mushtak Al-atabi; PRP Hoole (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The electrical and thermal energy generated by a Photo-voltaic (PV) module is based on the amount of the solar radiation directed on the PV module. In this study, a Photo-voltaic Thermal (PVT) system is constructed to maximize the electrical energy generation through the fast removal of heat through a new phase layered topology. The combinations of aluminum plate and heatsinks are used to transfer heat generated by sunlight radiation on PV modules to heat transfer thermal container. The aluminum plate is attached beneath the PV module and heatsinks welded beneath the alumni plate making it as a phase layered heat removal. The heat transfer on each layer of the photovoltaic thermal system is investigated with the phase changing topology and also investigated for its performance with a heat removal agent. In both cases, with and without water as coolant in the thermal container, the experimental outcome is analysed for performance analysis. It is found the PV temperature reduced by about 10 degrees which is cirtical for the PV performance reducing the wasted thermal energy and thereby increases the electrical energy conversion.